Red Light Phototherapy Using Light-Emitting Diodes Inhibits Melanoma Proliferation and Alters Tumor Microenvironments - Austin, Evan; Huang, Alisen; Wang, Jennifer Y.; Cohen, Marc; Heilman, Edward; Maverakis, Emanual; Michl, Josef; Jagdeo, Jared (Frontiers in Oncology, 2022)
Background: Total annual cancer rates have decreased due to improved treatment and prevention. However, the incidence of melanoma is rising, and not all patients respond to immune and targeted approaches. Therefore, we sought to determine the efficacy of red light (RL) phototherapy in preclinical models of melanoma. Methods: Melanoma cells (A375, B16F10, MNT-1) were irradiated with RL. Melanoma proliferation, apoptosis, oxidative stress, and p53 phosphorylation were measured in vitro. In C57BL/6 mice, phototherapy safety, B16F10 tumor growth, and immunocyte infiltration were assessed following RL. Results: In vitro, 640 J/cm2 RL decreased cellular proliferation without increasing apoptosis, while 1280 J/cm2 increased apoptosis. RL increased intracellular reactive oxygen species generation and p53 phosphorylation. In animal models, 2560 J/cm2 RL significantly prevented melanoma growth and increased the expression of CD103+ dendritic cells. 1280 and 1920 J/cm2 RL decreased tumor volume, but not significantly. RL did not cause skin inflammation or erythema in normal skin. Conclusion: RL represents a potentially safe and effective melanoma therapeutic. RL prevented tumor growth and increased the expression of immune markers, such as CD103, that are associated with favorable melanoma outcomes. Further research is needed to determine the optimal clinical treatment regimen for melanoma using RL.